2011
DOI: 10.4049/jimmunol.1002711
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Alterations of α7 Nicotinic Receptor in Colonic CD4 T Cells Mediate Dichotomous Response to Nicotine in Murine Models of Th1/Th17- versus Th2-Mediated Colitis

Abstract: Ulcerative colitis (UC) and Crohn’s disease (CD) are two forms of chronic inflammatory bowel disease. CD4 T cells play a central role in the pathogenesis of both diseases. Smoking affects both UC and CD but with opposite effects, ameliorating UC and worsening CD. We hypothesized that the severity of gut inflammation could be modulated through T-cell nicotinic acetylcholine receptors (nAChRs) and that the exact clinical outcome would depend on the repertoire of nAChRs on CD4 T cells mediating each form of colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 86 publications
4
76
0
Order By: Relevance
“…76 Although there is no clear explanation for this difference, a recent report using two models of murine colitis mimicking Th1 or Th2 type of inflammation has shown that the divergent effect of nicotine may be explained by the upregulation of the α7nAChR by a Th2 inflammatory response (ulcerative colitis) but not by a typical Th1/Th17 inflammatory response. 77 Assuming that the therapeutic response of nicotine (or smoking) is mediated by α7nAChR, these findings may explain the differential effect of smoking in Crohn's versus ulcerative colitis patients. To what extent this difference in α7nAChR expression also applies to IBD patients remains to be investigated.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…76 Although there is no clear explanation for this difference, a recent report using two models of murine colitis mimicking Th1 or Th2 type of inflammation has shown that the divergent effect of nicotine may be explained by the upregulation of the α7nAChR by a Th2 inflammatory response (ulcerative colitis) but not by a typical Th1/Th17 inflammatory response. 77 Assuming that the therapeutic response of nicotine (or smoking) is mediated by α7nAChR, these findings may explain the differential effect of smoking in Crohn's versus ulcerative colitis patients. To what extent this difference in α7nAChR expression also applies to IBD patients remains to be investigated.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Nizri et al also demonstrated that nicotine treatment inhibited the response of Th1 and Th17 cells and attenuated neuroinflammation in autoimmunity encephalomyelitis [17]. Nicotine treatment could ameliorate inflammatory bowel disease severity through increasing the proportion of Treg cells and decreasing the proportion of Th17 cells [11]. In this research, we proposed that the CAP could regulate the differentiation of CD4 + T cells in viral myocarditis.…”
Section: Discussionmentioning
confidence: 82%
“…Our previous studies have indicated that the CAP significantly decreases the level of Th17 cell-related IL-17A and IL-6 as well as Th1 cell-associated TNF-α [610]. Galitovskiy et al also found that α7-nicotinic acetylcholine receptor (α7-nAChR) agonist, nicotine, increased the ratio of Treg cells and reduced the ratio of Th17 cells, improving the prognosis of ulcerative colitis [11]. These results suggest that CAP may regulate the differentiation of CD4 + T cells in VMC mice.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine was shown to abrogate oxazolone -colitis via the up regulation of colonic Treg cells and decreased TH17 although TNBS-colitis was exacerbated with an elevation of TH17 cells in the colon. They suggested that nicotinic receptors expressed bispecific action by stimulating IL-10 release and attenuating IL-17 secretion or stimulating IL-17 production which confirmed that smoking could induce opposing effects in CD and UC affected individuals [29].…”
Section: The Influence Of Th17 Cells On Ibdmentioning
confidence: 93%